Maize Metabolic Network Construction and Transcriptome Analysis. Issue 1 (1st March 2013) - Monaco, Marcela K.; Sen, Taner Z.; Dharmawardhana, Palitha D.; Ren, Liya; Schaeffer, Mary; Naithani, Sushma; Amarasinghe, Vindhya; Thomason, Jim; Harper, Lisa; Gardiner, Jack; Cannon, Ethalinda K.S.; Lawrence, Carolyn J.; et al.
Abstract : A framework for understanding the synthesis and catalysis of metabolites and other biochemicals by proteins is crucial for unraveling the physiology of cells. To create such a framework for Zea mays L. subsp. mays (maize), we developed MaizeCyc, a metabolic network of enzyme catalysts, proteins, carbohydrates, lipids, amino acids, secondary plant products, and other metabolites by annotating the genes identified in the maize reference genome sequenced from the B73 variety. MaizeCyc version 2.0.2 is a collection of 391 maize pathways involving 8889 enzyme mapped to 2110 reactions and 1468 metabolites. We used MaizeCyc to describe the development and function of maize organs including leaf, root, anther, embryo, and endosperm by exploring the recently published microarray‐based maize gene expression atlas. We found that 1062 differentially expressed metabolic genes mapped to 524 unique enzymatic reactions associated with 310 pathways. The MaizeCyc pathway database was created by running a library of evidences collected from the maize genome annotation, gene‐based phylogeny trees, and comparison to known genes and pathways from rice ( Oryza sativa L.) and Arabidopsis thaliana (L.) Heynh. against the PathoLogic module of Pathway Tools. The network and the database that were also developed as a community resource are freely accessible online at http://maizecyc.maizegdb.org to facilitate analysis and promote studies on metabolic genes in maize.